1990
DOI: 10.1111/j.1348-0421.1990.tb00991.x
|View full text |Cite
|
Sign up to set email alerts
|

Demonstration of a Surface Antigen of Clostridium tyrobutyricum by Use of Immunoblotting with a Monoclonal Antibody

Abstract: A monoclonal antibody,

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

1994
1994
1998
1998

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 21 publications
0
1
0
Order By: Relevance
“…Our first study showed the existence of a surface antigen with a ladder pattern closely similar in appearance to the lipopolysaccharide of Gram-negative bacteria when examined by SDS-PAGE. The inhibition of the antigen reactivity to a MoAb (AC2-41) after mild periodate oxidation sug-gests the involvement of a carbohydrate moiety in the epitope (16 twice with phosphate-buffered saline (PBS: 0.137 M NaCl; 2.7 X 10-3 M KO; 1.47 X 10-3 M K.H2PO4; 0.067 M Na2HPO4, 2H20) at pH 7.0. Antigen extraction (6).…”
Section: Introductionmentioning
confidence: 99%
“…Our first study showed the existence of a surface antigen with a ladder pattern closely similar in appearance to the lipopolysaccharide of Gram-negative bacteria when examined by SDS-PAGE. The inhibition of the antigen reactivity to a MoAb (AC2-41) after mild periodate oxidation sug-gests the involvement of a carbohydrate moiety in the epitope (16 twice with phosphate-buffered saline (PBS: 0.137 M NaCl; 2.7 X 10-3 M KO; 1.47 X 10-3 M K.H2PO4; 0.067 M Na2HPO4, 2H20) at pH 7.0. Antigen extraction (6).…”
Section: Introductionmentioning
confidence: 99%